The relationship between peer conformity and aggressiveness tendencies in vocational students - Silvia, Silvia; Ardi, Zadrian (International Journal of Applied Counseling and Social Sciences, 2024)
This research is motivated by the problem of student aggressiveness at school such as the number of students who follow their friends in insulting and hitting other students who have problems with their group of friends. Peer conformity is one of the factors that influence the tendency of aggressiveness. The purpose of this study is to describe the relationship between peer conformity and aggressiveness tendencies in vocational students. This study uses quantitative methods with descriptive correlational research. The study population was 393 students enrolled in class XI of SMK Negeri 5 Padang in the July-December semester of the 2024/2025 academic year with a sample of 199 students determined by Proportional Random Sampling technique. Data collection using a Likert model scale. Data were analyzed using descriptive statistical techniques and Pearson Product Moment correlation techniques. The results of this study indicate that: (1) peer conformity is in the moderate category, (2) aggressiveness tendencies are in the low category, and (3) there is a positive and significant relationship between peer conformity and aggressiveness tendencies with a correlation coefficient of 0.411 and a significant level of 0.001. The implications of the research results for Guidance and Counseling are by providing information services, individual counseling services, and group guidance services.